Multiferroic properties of Bi0.5K0.5TiO3–BiFe1−xCoxO3 (0 ≤ x ≤ 0.2) solid solution. Issue 126 (11th December 2015) - Zuo, X. Z.; Yang, J.; Yuan, B.; Kan, X. C.; Zu, Lin; Qin, Y. F.; Zhu, X. B.; Song, W. H.; Sun, Y. P.
Abstract : We have successfully prepared a binary lead-free solid-solution of Bi0.5 K0.5 TiO3 –BiFe1− x Co x O3 using a modified Pechini method and investigated the magnetic and ferroelectric properties of Bi0.5 K0.5 TiO3 –BiFe1− x Co x O3 (0 ≤ x ≤ 0.2). Abstract : The fabrication of BiFeO3 and Bi0.5 K0.5 TiO3 typically encounters problems with densification and phase purity, requiring conditions of high pressure for the synthesis of bulk phases. In this letter, we have successfully prepared a binary lead-free solid-solution of Bi0.5 K0.5 TiO3 –BiFe1− x Co x O3 using a modified Pechini method and investigated the magnetic and ferroelectric properties of Bi0.5 K0.5 TiO3 –BiFe1− x Co x O3 (0 ≤ x ≤ 0.2). The coexistence of room-temperature ferromagnetism and ferroelectricity is observed in Bi0.5 K0.5 TiO3 –BiFe1− x Co x O3 (0.5 ≤ x ≤ 0.2). The x = 0.2 sample exhibits ferromagnetic behavior with a Curie temperature T C of 661 K, compared with the paramagnetic like behavior exhibited in Bi0.5 K0.5 TiO3 –BiFeO3 at room temperature. The ferromagnetism can be ascribed to the suppression of a spiral spin structure with the canting of the anti-ferromagnetically ordered spins caused by structural distortion due to the substitution of Co ions. The x = 0.2 sample also exhibits a well-defined ferroelectric hysteresis loop with a rather large remnant polarization ( P r = 32.72 μC cm −2 ), which is superior to that of other lead-free ferroelectric compounds. The improved ferroelectric properties can be attributed to the increased grain size and lattice distortion caused by Co doping. The observation of room temperature ferromagnetism and ferroelectricity for Bi0.5 K0.5 TiO3 –BiFe1− x Co x O3 suggests that these materials are potential candidates for multiferroic materials and ferroelectric memory devices.